The functional roles of species in metacommunities, as revealed by metanetwork analyses of bird–plant frugivory networks. (20th May 2020) - Li, Hai‐Dong; Tang, Linfang; Jia, Chenxi; Holyoak, Marcel; Fründ, Jochen; Huang, Xiaoqun; Xiao, Zhishu
Abstract: Understanding how biodiversity and interaction networks change across environmental gradients is a major challenge in ecology. We integrated metacommunity and metanetwork perspectives to test species' functional roles in bird–plant frugivory interactions in a fragmented forest landscape in Southwest China, with consequences for seed dispersal. Availability of fruit resources both on and under trees created vertical feeding stratification for frugivorous birds. Bird–plant interactions involving birds feeding only on‐the‐tree or both on and under‐the‐tree (shared) had a higher centrality and contributed more to metanetwork organisation than interactions involving birds feeding only under‐the‐tree. Moreover, bird–plant interactions associated with large‐seeded plants disproportionately contributed to metanetwork organisation and centrality. Consequently, on‐the‐tree and shared birds contributed more to metanetwork organisation whereas under‐the‐tree birds were more involved in local processes. We would expect that species' roles in the metanetwork will translate into different conservation values for maintaining functioning of seed‐dispersal networks. Abstract : Bird-plant interactions involving birds feeding only on the tree or both on and under the tree had a higher centrality and contributed more to metanetwork organization than interactions involving birds feeding only under the tree. Moreover, bird-plant interactions associated with large-seeded plants disproportionately contributed to metanetwork organization and centrality. Consequently, on-the-tree and shared birds contributed more to metanetwork organization whereas under-the-tree birds were more involved in local processes.